STUDY OF THE IMPACT OF MINERAL SALTS, INCUBATION TIME AND AERATION ON BY BACILLUS SP. (STRAIN RL1) ON XYLANASE PRODUCTION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This study used Bacillus sp. (Strain RL1), six distinct mineral salts (LiCl, K2HPO4, KCl, CaCl2, ZnSO4, and CuSO4), and five incubation times (24, 48, 72, 96, and 120 hours) to investigate the xylanase enzyme synthesis. The method of measuring xylanase activity involved assaying dinitrosalicylic acid. the highest enzymatic activity was obtained from the use of K2HPO4, which reached, 0.5722 U/ml, followed by CaCl2, as the enzymatic activity reached 0.5682 U/ml, and CuSO4 gave the lowest, Enzymatic effectiveness reached 0.2816 U/ml, while the enzymatic effectiveness of using LiCl, KCl and ZnSO4 was (0.2644, 0.3588 and 0.362 U/ml), respectively. the enzymatic activity of the xylanase produced increased with increasing incubation period, reaching 0.486 U/ml after 24 hours, reaching its maximum level of 0.681 U/ml after 96 hours of incubation. It returns and decreases as the incubation period increases, reaching 0.376 after 120 hours of incubation. While aeration, the highest enzymatic effectiveness of the xylanase enzyme was 0.681 U/ml when the shaking incubator was used at 200 rpm after 96 hours of incubation time.